The Godfather - S. Ruddy, Albrt; Coppola, Francis Ford; Paramount Pictures (California : Paramount Pictures, 1972)
The complete saga of the Mafia Corleone family, from Don Corleone's childhood in Sicily, his son Michael Corleone's rise to power and finally the struggle to succeed him
Based on Mario Puzo's best selling novel'The Godfather'
Title from title screen
Subtitles in English
Music scored by Nino Rota ; screenplay by Mario Puzo and Francais Ford Coppola
Cast : Marlon Brando, Al Pacino James Caan, Richard Castellano, Robert Duvall, Sterling Hayden, John Marley, Richard Conte, Diane Keaton
Keywords: Puzo, Mario, -- 1920- -- Film and video adaptations; Mafia -- Drama; Gangster films